Phylogeny of the Ferungulata (Mammalia: Laurasiatheria) as determined from phylogenomic data - Hou, Zhuo-cheng (2009)
Great progress has been made toward resolving the evolutionary relationships among extant mammals, yet there are still areas of disagreement. The relationships among ferungulates that have high quality draft genome sequences available (i.e. dog, cow, horse) are unresolved, and thus we examined their phylogeny using currently known mammalian 1:1 orthologs. This dataset consists of 40 million base pairs from 2705 protein-coding genes. Maximum likelihood and Bayesian analyses of the combined and individual gene phylogenies strongly support a sister grouping of cow and horse to the exclusion of dog although topology tests could not rule out a horse and dog sister group relationship.